(untitled) (Bioscience Journal, 2020)
H. impetiginosus belongs to the Bignoniaceae family; it has a great potential for economic exploitation and can be used in landscaping of urban areas, reforestation, recovery of degraded areas, and folk medicine. The experiment was carried out to evaluate the effect of light and temperature regimes on the germination and vigor of Handroanthus impetiginosus seeds at the Seed Analysis Laboratory of UFRPE/UAG. The seeds were subjected to light regimes: white, far red, red, and no light at 15°C, 20°C, 25°C, 30°C, 35°C, and 40°C, using a completely randomized experimental design in a factorial scheme (4 × 6), with four repetitions of 25 seeds. The different light regimes did not influence the seed germination of H. impetiginosus. The highest germination percentage (92%) and germination speed index (7.94) were obtained at temperatures 28.2°C and 29.2°C, respectively, both under red light. The longest seedling length was also obtained from the seeds subjected to red light regime at 25°C. The temperatures of 15°C and 40°C inhibited the germination of H. impetiginosus seeds. H. impetiginosus seeds are classified as neutral photoblastics, and constant temperatures of 28.2°C and 29.2°C provided maximum germination.